Stable and reversible pressure-controlled dielectric switching in dicyanide hybrid perovskite. (March 2021) - Szeremeta, Anna Z.; Nowok, Andrzej; Pawlus, Sebastian; Fedoruk, Katarzyna; Trzebiatowska, Monika; Mączka, Mirosław; Symonowicz, Joanna; Paluch, Marian; Sieradzki, Adam
Highlights: Possibility of dielectric switching by using external pressure for dicyanide. Pressure-induced phase transition hysteresis occurring in PyrKCO. Reversible and stable switching under hydrostatic pressure. PyrKCO as promising material for temperature-pressure dielectric switcher. Abstract: Fast ON/OFF switches are the basis of contemporary microelectronics. Dielectrics alternating between high and low dielectric permittivity states (ON and OFF, respectively) seem to be up-and-coming candidates for efficient switches. Currently, the change of their state is induced by a temperature gradient, which is a relatively slow process. In this paper, for the first time, we demonstrate fast switching in polycrystalline [(CH2 )4 NH2 ]2 [KCo(CN)6 ] perovskite thanks to the incorporation of pressure as one of the switching parameters. Our results show that material's dielectric response depends on an applied temperature-stress thermodynamical path. Moreover, our switches show high state retention and durability in both ON and OFF states under ambient and high pressures. Our findings open new prospects in the development of efficient dielectric switches. Graphical abstract: Image, graphical abstract